Comparing the Effect of Strengthening the Square Lumbar Muscle in Increasing the Record Number of Squats of Volleyball Players in Ardabil Province - Amir Jafarnezhadgero; Mehrdad Moharramzadeh; Aydin Ali Khiavi; Farzad Nobakht (Islamic Azad University, Hamedan Branch, 2022)
Objective: Scott training is one of the basic exercises in strengthening the lower limbs and also a factor to show a person's physical fitness. The aim of the present study was to compare the effect of strengthening the lumbar quadriceps muscle in increasing the record number of squats of male volleyball players in Ardabil province. Methods: A total of 60 healthy volleyball athletes from Ardabil province were randomly divided into two equal groups of 30 intervention and control. Both groups were presented with the usual volleyball bodybuilding training method for 12 sessions, respectively, with strengthening the quadriceps muscle, as well as just the usual volleyball bodybuilding training. After 12 sessions, their record number of Scott moves was examined. Independent t-test was used to compare the groups's record number of squats using SPSS software version 26. Results: The findings of the present study showed that there is a statistically significant difference between the intervention group and the control one in the frequency of Scott's record of volleyball athletes (P≤0.001).  Conclusion: Providing reinforcement training increased Scott's record in the intervention group. Therefore, strengthening the lumbar quadriceps muscle can increase the frequency of Scott's record in male volleyball athletes in Ardabil province.